2009
DOI: 10.1007/s10278-009-9220-x
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Organization of Hospital Medical Imaging: A User Satisfaction Survey

Abstract: A virtual medical imaging department is an innovative and demanding organizational model, to the extent that the underlying goal is to achieve a continuous and advanced organizational integration of human and physical resources, clinical data, and clienteles. To better understand the kind of benefits offered, we conducted a survey of three groups of users-radiologists, radiological technologists, and medical specialists-working in a five-site virtual organization. We received 127 valid questionnaires, for an o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 26 publications
2
12
0
Order By: Relevance
“…The results of SEM showed that almost all hypotheses were supported. These results were consistent with that presented in Sicotte et al [21]. However, both information quality and service quality didn't affect intention to use significantly.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The results of SEM showed that almost all hypotheses were supported. These results were consistent with that presented in Sicotte et al [21]. However, both information quality and service quality didn't affect intention to use significantly.…”
Section: Discussionsupporting
confidence: 92%
“…The D&M IS success model has also been applied in some studies of health information systems [21,22]. However, it has seldom been used to explain the success of telehealth.…”
Section: Dandm Is Success Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…It stands to reason that the greater the number of functionalities available in a system, the greater the potential for their exploration, assimilation and appropriation by physicians [ 34 , 35 ]. For example, Sicotte et al [ 36 ] found that physicians were more satisfied with a PACS system when they perceived it to be more useful, i.e. when it provided “a complete range of functionalities” in support of their work, was “well harmonized” with their clinical practices, and was “compatible” with all aspects of their tasks.…”
Section: Introductionmentioning
confidence: 99%
“…Use of this model is supported by a well-researched and validated measurement inventory, notably in health care (e.g. Sicotte, Paré, Bini, Moreault, & Laverdure, 2010;Van Der Meijden, Tance, Troost, & Hasman, 2003). The same questionnaire was used for the pre-and post-periods.…”
Section: Measures Of User Attitudesmentioning
confidence: 99%